New-onset supraventricular arrhythmia during septic shock: prevalence, risk factors and prognosis - Seemann, Aurélien (Ann Intensive Care, 2015)
BACKGROUND: The aims of this study were to prospectively assess the prevalence of sustained (lasting more than 30 s) new-onset supraventricular arrhythmia (NOSVA) during septic shock, identify the associated factors (including septic myocardial dysfunction), and evaluate its impact on hemodynamics and prognosis. METHODS: Patients with a diagnosis of septic shock were screened in a medical intensive care unit of a tertiary hospital center in France with a continuous 12-lead EKG for the occurrence of NOSVA. Biological and clinical data (including septic myocardial dysfunction characterized by echocardiography) were collected. We also assessed the hemodynamic tolerance and prognosis of NOSVA. RESULTS: Among the 71 septic shock episodes assessed during the study, NOSVA occurred in 30 [prevalence of 42 %, 95 % confidence interval (CI) 30–53 %]. Among all recorded factors, only renal failure (as assessed by renal SOFA score at day 1) was associated with NOSVA and this difference persisted by multivariable analysis (odds ratio of 1.29, 95 % CI 1.03–1.62, p = 0.03). There was a significant increase in norepinephrine dosage during the first hour after SVA onset. NOSVA was associated with longer catecholamine use during septic shock as compared with patients in sinus rhythm, whereas ICU mortality was identical between groups. CONCLUSIONS: We found a high prevalence of sustained NOSVA during septic shock. NOSVA was not related to septic myocardial dysfunction, but rather to acute renal failure, raising the hypothesis of an acute renocardiac syndrome.